Kolaborasi Komunitas: Mengakselerasi Minat Renang Di Merauke Melalui Pengabdian Masyarakat - Samel Watina Ririhena; Yosephina Ohoiwutun; Beatus Tambaip; Pande Made Dharma Sanjaya; Okto Irianto; Pulung Riyanto (Institut Nalanda, 2023)
This research discusses a Community Collaboration that aims to accelerate interest in swimming in Merauke through community service. A brief introduction explains the background of the low interest in swimming and the constraints faced by the people of Merauke. The research objective is to describe the impact of this collaboration on swimming awareness, participation, culture and accessibility in Merauke. The research method included a collaborative approach involving swimming coaches, government agencies, community organizations, and the private sector. Training programs and outreach campaigns were run to increase community awareness of the benefits of swimming. Data analysis involved participation monitoring, community view surveys, and impact evaluation. The results showed a significant increase in public awareness of the importance of swimming, especially in terms of safety and health. Participation in swimming activities also increased significantly across different age groups. The establishment of a positive swimming culture is also one of the outcomes of this collaboration, where swimming is no longer considered as an alien thing but a part of the daily routine. The construction of public swimming facilities and the provision of adequate swimming equipment have also successfully overcome infrastructure barriers, providing easier access for the community. This article illustrates how community collaboration can transform.